Distinct Associations of HbA1c and the Urinary Excretion of Pentosidine, an Advanced Glycosylation End-product, with Markers of Endothelial Function in Insulin-dependent Diabetes mellitus - Smulders, Ronald A.; Stehouwer, Coen D. A.; Schalkwijk, Casper G.; Donker, Ab J. M.; van Hinsbergh, Victor W. M.; TeKoppele, Johan M. (Thrombosis and Haemostasis, 1998)
Dysfunction of the vascular endothelium is considered an early step in the development of diabetic angiopathy. Hyperglycaemia results in endothelial dysfunction, both through direct effects of glucose and through formation of advanced glycosylation end-products (AGEs). We hypothesized that the effects of glucose and AGEs on endothelial function in insulin-dependent diabetes mellitus (IDDM) are distinct and are reflected by distinct plasma markers of endothelial function. We therefore measured plasma levels of von Willebrand factor (vWF), soluble (s) E-selectin and vascular cell adhesion molecule-1 (sVCAM-1), and evaluated the relationship with HbA1c and urinary excretion of pentosidine, an AGE product, in 56 patients with IDDM. Urinary pentosidine excretion was higher in the diabetic than in a control group (n = 60) of similar age (P <0.0001) and showed a steeper increase with age (P <0.02 vs controls). In the diabetic group, sE-selectin was correlated to HbA1c (r = 0.52, P <0.0001), whereas sVCAM-1 was not (r = 0.11, P = 0.47). In contrast, sVCAM-1 showed a trend towards a correlation with log (pentosidine excretion) (r = 0.27, P = 0.06), whereas sE-selectin did not (r = –0.16, P = 0.27). Log(vWF) was correlated to HbA1c (r = 0.50, P <0.0001) and tended to correlate with log (pentosidine excretion) (r = 0.25, P = 0.07). Multivariate analyses with both pentosidine and HbA1c as independent variables showed significant associations of sE-selectin with HbA1c, of sVCAM-1 with pentosidine, and of log(vWF) with both HbA1c and pentosidine (all P-values <0.02). Our results imply that the effects of glucose and AGEs on the endothelium can be reflected by distinct endothelial markers. Plasma sE-selectin may reflect short-term effects of glucose on the endothelium, sVCAM-1 the effects of AGEs, and vWF the combined effect of glucose and AGEs.